Modernisasi Administrasi Perpajakan: NIK Menjadi NPWP - Even Gio Lumban Tobing; Kusmono kusmono (JURNAL PAJAK INDONESIA, 2022)
Indonesia will enter an era where one identity card can be used for various administrative matters, this is marked by the application of NIK to become NPWP. The application of NIK to NPWP is also known as the Single Identity Number system. Single Identity Number is believed to be able to simplify the tax administration system and build a strong database for the government. This study aims to look at the estimation of the fulfillment of the principles of simplicity and benefit with the application of NIK to become NPWP for Individual Taxpayers as stated in Law Number 7 of 2021 concerning Harmonization of Tax Regulations.